Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment

By forming a double-layer cladding layer on the secondary particles of the positive electrode material of the lithium-ion battery, the thickness of the cladding layer is controlled, and the problem of peeling and damage of the positive electrode material after the increase in the number of cycles is solved, which significantly improves the cycling performance and stability of the battery.

CN119695117APending Publication Date: 2025-03-25JIANGSU DANGSHENG MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411895670.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials are prone to in-plane peeling and damage after the number of cycles increases, resulting in attenuation of battery capacity. The existing coating technology has poor effect on improving the cycle performance of the battery.

Method used

A positive electrode active material is proposed, which includes secondary particles formed by agglomeration of primary particles and a double-layer cladding formed on the surface thereof. The average thickness of the first cladding layer and the second cladding layer is controlled between 0.5 nm-10 nm and 3 nm-20 nm, respectively. The thickness of the second cladding layer is greater than that of the first cladding layer. This structure reduces particle cracks and damage, blocks side reactions of the electrolyte, and maintains normal transmission of lithium ions.

Benefits of technology

Through the design of the double-layer cladding layer, the particle cracks and damage of the positive electrode active material are significantly reduced, the side reaction between the electrolyte and the material is blocked, and the stability of the material and the circulation performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695117A_ABST
    Figure CN119695117A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode active material and a preparation method thereof, a positive electrode plate, a battery and electric equipment, and relates to the technical field of batteries, the positive electrode active material comprises a body and a coating layer formed on at least part of the surface of the body, the body is secondary particles formed by agglomeration of primary particles, and the coating layer is formed on at least part of the surface of the body. The coating layer comprises a first coating layer and a second coating layer, the first coating layer is formed on at least part of the first surface of the primary particle, and the second coating layer is formed on the second surface of the primary particle; the average thickness of the first coating layer ranges from 0.5 nm to 10 nm, the average thickness of the second coating layer ranges from 3 nm to 20 nm, and the average thickness of the second coating layer is larger than that of the first coating layer. Therefore, the battery containing the positive electrode active material has excellent capacity and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular relates to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] The main components of lithium-ion batteries are electrolyte, diaphragm materials, positive electrode and negative electrode materials. Among them, the performance of the positive electrode of lithium-ion batteries directly affects the electrochemical performance of lithium-ion batteries. Taking ternary materials as an example, they have the advantages of high energy density, high specific capacity, low cost, good stability, etc., making them one of the most promising positive electrode active materials for lithium batteries. However, with the increase in the number of cycles, the particles of ternary materials are often prone to in-plane peeling and damage, which will lead to a decrease in the surface area of ​​the positive electrode and ultimately lead to a decrease in the battery capacity. In order to reduce the capacity decay of the battery. Surface coating has become one of the effective means to optimize the electrochemical properties of the positive electrode active material. However, the existing coating technology has a poor effect on improving the cycle performance of the battery. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art to at least some extent. To this end, one object of the present invention is to provide a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device, wherein the battery containing the positive electrode active material has excellent cycle performance.

[0004] In one aspect of the present invention, the present invention proposes a positive electrode active material, which includes a body and a coating layer formed on at least a portion of the surface of the body, the body is a secondary particle formed by agglomeration of primary particles, the coating layer includes a first coating layer and a second coating layer, the first coating layer is formed on at least a portion of the first surface of the primary particle, and the second coating layer is formed on the second surface of the primary particle; the average thickness of the first coating layer is 0.5nm-10nm, the average thickness of the second coating layer is 3nm-20nm, and the average thickness of the second coating layer is greater than the average thickness of the first coating layer.

[0005] According to the positive electrode active material of the embodiment of the present invention, by setting a coating layer on the main body of the positive electrode active material and controlling the average thickness of the first coating layer and the second coating layer, it is sufficient to reduce the occurrence of particle cracks and damage of the main body, and within the average thickness range of the first coating layer and the second coating layer, it can prevent the main body from having side reactions with the electrolyte without affecting the normal transmission of lithium ions. In addition, making the average thickness of the second coating layer greater than the average thickness of the first coating layer can make the surface of the positive electrode active material smoother, reduce the probability of the electrolyte entering the interior of the main body, further reduce the probability of the positive electrode active material having side reactions with the electrolyte, and improve the stability of the positive electrode active material. In summary, the positive electrode active material proposed in this application and the battery containing it have excellent cycle performance.

[0006] In addition, the positive electrode active material according to the above embodiment of the present invention may also have the following additional technical features:

[0007] In some embodiments of the present invention, the average thickness of the first coating layer is 2nm-5nm.

[0008] In some embodiments of the present invention, the average thickness of the second coating layer is 5nm-12nm.

[0009] In some embodiments of the present invention, the difference between the average thickness of the second coating layer and the average thickness of the first coating layer is 2.0 nm-15.0 nm, preferably 3 nm-7 nm.

[0010] In some embodiments of the present invention, the average thickness of the coating layer is 1 nm-20 nm, preferably 2 nm-6 nm.

[0011] In some embodiments of the present invention, the convexity R of the positive electrode active material is (BET2-BET1) / BET1, wherein BET2 is the specific surface area of ​​the positive electrode active material measured by the N2 adsorption method, BET1=6 / (ρ×Dv50), ρ is the tap density of the positive electrode active material, and Dv50 is the median particle size of the particle size volume distribution of the positive electrode active material; the convexity R=0.1-2.0, preferably 0.3-0.8. Therefore, the secondary particles in the present application have a smaller convexity, indicating that the surface of the coated secondary particles is relatively flat, the concave-convex structure caused by the primary particles is less, and the structural uniformity is good, which is conducive to reducing the polarization of the positive electrode active material, improving the ion transport performance, and improving the rate performance and cycle performance of the battery.

[0012] In some embodiments of the present invention, BET2 = 0.3 m 2 / g-0.9m 2 / g; preferably 0.4m 2 / g-0.5m 2 / g.

[0013] In some embodiments of the present invention, BET1 = 0.23 m 2 / g-0.4m 2 / g.

[0014] In some embodiments of the present invention, ρ = 1.5 g / cm 3 -2.9g / cm 3 .

[0015] In some embodiments of the present invention, Dv50=3 μm-18 μm.

[0016] In some embodiments of the present invention, the body comprises Li 1+a Ni x Co y Mn z M w O2, wherein M includes at least one of V, Ti, W, Mg, Y, Zr, and Al, -0.1≤a≤0.2, 0.5≤x<1.0, 0<y≤0.2, 0<z≤0.3, and 0≤w≤0.015.

[0017] In some embodiments of the present invention, the coating layer includes lithium vanadium oxide.

[0018] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned positive electrode active material, comprising:

[0019] Mixing a hydroxide precursor with a lithium source and sintering for the first time to obtain a body, wherein the hydroxide precursor includes Ni element, Co element, Mn element and optionally M element;

[0020] The main body is mixed with the material containing the coating layer and water, heated and stirred until the water is evaporated, and sintered for the second time to obtain the positive electrode active material.

[0021] Thus, the above-mentioned positive electrode active material can be prepared by this method, and the average thickness of the first coating layer and the second coating layer can be controlled, which is sufficient to reduce the occurrence of particle cracks and damage of the main body, and within the average thickness range of the first coating layer and the second coating layer, it can prevent the main body from having side reactions with the electrolyte without affecting the normal transmission of lithium ions. In addition, making the average thickness of the second coating layer greater than the average thickness of the first coating layer can make the surface of the positive electrode active material smoother, further reducing the probability of side reactions between the positive electrode active material and the electrolyte, and improving the stability of the positive electrode active material. In summary, the positive electrode active material proposed in this application and the battery containing it have excellent cycle performance.

[0022] In some embodiments of the present invention, the ratio of the mass of the body, the mass of the material containing the coating layer and the volume of the water is 1 g: (0.01-0.12) g: 100 mL, preferably 1 g: (0.03-0.10) g: 100 mL.

[0023] In some embodiments of the present invention, the temperature of the second sintering is 200°C-600°C, preferably 300°C-500°C.

[0024] In some embodiments of the present invention, the coating-containing material includes polyvanadate.

[0025] In some embodiments of the present invention, the polyvanadate comprises Na6V 10 O 28 12H2O, K6V 10 O 28 At least one of 9H2O and NH4VO3.

[0026] In some embodiments of the present invention, the temperature of the first sintering is 700°C-900°C.

[0027] In some embodiments of the present invention, the heating temperature is 100°C-200°C.

[0028] In some embodiments of the present invention, the stirring speed is 60r / min-600r / min.

[0029] In some embodiments of the present invention, the second sintering time is 2h-10h.

[0030] In a third aspect of the present invention, the present invention provides a positive electrode sheet, comprising the positive electrode active material described in the first aspect of the present invention.

[0031] In the fourth aspect of the present invention, the present invention provides a battery, comprising the positive electrode sheet described in the third aspect of the present application, so that the battery has excellent capacity and cycle performance.

[0032] In a fifth aspect of the present invention, the present invention provides an electrical device comprising the battery described in the fourth aspect of the present invention.

[0033] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope image of the positive electrode active material prepared in Example 1 of the present application;

[0035] Figure 2This is a voltage curve of the battery obtained in Example 2 of the present application under 0.1C charge and discharge conditions in the second cycle;

[0036] Figure 3 1 is a graph of the discharge capacity of the battery of Example 4 of the present application at different rates and cycle numbers;

[0037] Figure 4 It is a cycle performance diagram of Example 4 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0038] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0039] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0040] In one aspect of the present invention, the present invention proposes a positive electrode active material, which includes a body and a coating layer formed on at least a portion of the surface of the body, the body is a secondary particle formed by agglomeration of primary particles, the coating layer includes a first coating layer and a second coating layer, the first coating layer is formed on at least a portion of the first surface of the primary particle, and the second coating layer is formed on the second surface of the primary particle; the average thickness of the first coating layer is 0.5nm-10nm, the average thickness of the second coating layer is 3nm-20nm, and the average thickness of the second coating layer is greater than the average thickness of the first coating layer.

[0041] As an example, the average thickness of the first cladding layer may be 0.5 nm, 1 nm, 3 nm, 5 nm, 7 nm, 10 nm, etc. According to some other embodiments of the present invention, the average thickness of the first cladding layer is 2 nm-5 nm.

[0042] The average thickness of the second cladding layer may be 3 nm, 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, etc. According to some other embodiments of the present invention, the average thickness of the second cladding layer is 5 nm-12 nm.

[0043] It can be understood that the first surface refers to the portion on the primary particle that will not form a gap with other primary particles on the same secondary particle; the second surface refers to the portion on the primary particle that can form a gap with adjacent primary particles on the same secondary particle.

[0044] The inventors found that by setting a coating layer on the main body of the positive electrode active material and controlling the average thickness of the first coating layer and the second coating layer, it is sufficient to reduce the occurrence of particle cracks and damage of the main body, and within the average thickness range of the first coating layer and the second coating layer, it can prevent the main body from having side reactions with the electrolyte without affecting the normal transmission of lithium ions; in addition, making the average thickness of the second coating layer in the gap between adjacent primary particles greater than the average thickness of the first coating layer can fill the gap between the primary particles to a certain extent, making the surface of the positive electrode active material smoother, reducing the probability of the electrolyte entering the interior of the main body, and reducing the contact area between the positive electrode active material and the electrolyte, further reducing the probability of side reactions between the positive electrode active material and the electrolyte, and improving the stability of the positive electrode active material. In summary, the positive electrode active material proposed in this application and the battery containing it have excellent cycle performance.

[0045] It can be understood that the embodiment of the present application uses an energy spectrum tester to test the integrated area of ​​the characteristic peak of the surface coating element of the positive electrode active material particle body, and the thickness of the coating layer = (integral area of ​​the characteristic peak of the coating element such as vanadium / integral area of ​​the characteristic peak of the standard containing the coating element) × the collection thickness of the standard containing the coating element.

[0046] When measuring the average thickness of the first coating layer, signal acquisition only selects the first surface coating layer area of ​​the primary particle; 10 primary particles on the surface of the secondary particle are randomly selected for testing, and then the average value is calculated, which is the average thickness of the first coating layer.

[0047] When testing the thickness of the second coating layer, signal acquisition only selects the coating layer of the gaps between the primary particles (second surface); then 10 primary particle gaps on the secondary particle surface are randomly selected for testing, and then the average value is calculated, which is the average thickness of the second coating layer.

[0048] According to an embodiment of the present invention, the difference between the average thickness of the second coating layer and the average thickness of the first coating layer is 2.0nm-15.0nm, for example, it can be 2.0nm, 4.8nm, 5.1nm, 10nm, 15.0nm, etc. The difference in the average thickness of the two coating layers is controlled within the above range, which is sufficient to reduce the occurrence of particle cracks and damage of the body, prevent the body from having side reactions with the electrolyte, ensure the normal transmission of lithium ions, and enhance the stability of the positive electrode active material, thereby improving the capacity and cycle performance. According to other embodiments of the present invention, the difference between the average thickness of the second coating layer and the average thickness of the first coating layer is 3nm-7nm.

[0049] According to an embodiment of the present invention, the average thickness of the coating layer is 1nm-20nm. For example, it can be 1nm, 3nm, 5nm, 10nm, 15nm, 20nm, etc. The average thickness of the coating layer refers to the average thickness of the coating layer containing the first coating layer and the second coating layer. Controlling the average thickness of the coating layer within the above range can isolate the electrolyte without affecting the transmission of lithium ions, improve the cycle stability of the material, and thus improve the cycle performance of the battery. According to other embodiments of the present invention, the average thickness of the coating layer is 2nm-6nm.

[0050] It can be understood that the average thickness of the coating can be determined by the following method: select a certain area on the surface of the positive electrode active material, measure the area proportion a of the first coating layer, the average thickness b of the first coating layer, the area proportion c of the second coating layer and the average thickness d of the second coating layer within the area, then the average thickness of the coating = a×b+c×d.

[0051] According to an embodiment of the present invention, the convexity R of the positive electrode active material is (BET2-BET1) / BET1, wherein BET2 is the specific surface area of ​​the positive electrode active material measured by the N2 adsorption method, BET1 is 6 / (ρ×Dv50), ρ is the tap density of the positive electrode active material, and Dv50 is the median particle size of the particle size volume distribution of the positive electrode active material; the convexity R is 0.1-2.0, preferably 0.3-0.8.

[0052] As an example, the concavo-convexity R may be 0.1, 0.5, 1, 1.5, 2, etc. According to some other embodiments of the present invention, R=0.3-0.8.

[0053] It can be understood that the specific calculation method of BET1 is: BET1 = theoretical surface area S of positive electrode active material particles / mass W of positive electrode active material particles = (4πr 2 ) / (volume V×tap density)=(4πr 2 ) / (4 / 3πr 3× tap density) = 3 / (r×tap density). Since r = Dv50 / 2, Dv50 is the median particle size of the particle size volume distribution of the positive electrode active material, it can be obtained that BET1 = 6 / (ρ×Dv50). BET2 is the specific surface area of ​​the positive electrode active material measured by the N2 adsorption method, which is close to the actual specific surface area of ​​the positive electrode active material. In this way, the concavity R can characterize the flatness of the surface of the positive electrode active material, that is, the larger the concavity, the more uneven the surface of the positive electrode active material, and the smaller the concavity, the flatter the surface of the positive electrode active material.

[0054] The convexity R of the positive electrode active material is controlled within the above range, and the convexity is reasonable, which means that the surface of the coated secondary particles is smoother than that of the main material before coating, and the concave-convex structure caused by the primary particles is less, and the structure is uniform, which is beneficial to reducing the polarization of the positive electrode material and improving the ion transport performance. The surface convexity is not too small to cause the average thickness of the coating layer to be too thick, thereby avoiding the impact of the coating layer on lithium ion transport and improving the battery's cycle performance and rate performance.

[0055] According to an embodiment of the present invention, BET2 = 0.3 m 2 / g-0.9m 2 / g. For example, BET2 can be 0.3m 2 / g,0.5m 2 / g,0.6m 2 / g,0.7m 2 / g,0.8m 2 / g,0.9m 2 According to some other embodiments of the present invention, BET2 = 0.4 m 2 / g-0.5m 2 / g.

[0056] According to an embodiment of the present invention, BET1 = 0.23 m 2 / g-0.4m 2 / g, for example, BET1 can be 0.23m 2 / g,0.25m 2 / g,0.3m 2 / g,0.35m 2 / g,0.4m 2 / g, etc.

[0057] According to an embodiment of the present invention, ρ = 1.5 g / cm 3 -2.9g / cm 3 For example, it can be 1.5 g / cm 3 , 2g / cm 3 , 2.5g / cm 3 , 2.9g / cm 3 wait.

[0058] According to an embodiment of the present invention, Dv50=3μm-18μm, for example, it can be 3μm, 5μm, 10μm, 15μm, 18μm, etc.

[0059] According to an embodiment of the present invention, the body comprises Li 1+a Ni x Co y Mn z M w O2, wherein M includes at least one of V, Ti, W, Mg, Y, Zr, and Al, -0.1≤a≤0.2, 0.5≤x<1.0, 0<y≤0.2, 0<z≤0.3, and 0≤w≤0.015.

[0060] As an example, a can be -0.1, 0, 0.1, 0.2, etc., x can be 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.98, etc., y can be 0.02, 0.05, 0.1, 0.15, 0.2, etc., z can be 0.02, 0.05, 0.1, 0.2, 0.3, etc., and w can be 0.005, 0.01, 0.015, etc.

[0061] The chemical formula of the main body adopts the above substances, which has the advantages of high energy density, high specific capacity, low cost, good stability performance, etc., which can further improve the cycle performance of the battery.

[0062] According to an embodiment of the present invention, the coating layer includes vanadium lithium oxide. Vanadium lithium oxide refers to an oxide containing vanadium and lithium elements. Since vanadium has a rich valence state and can undergo multi-electron redox reactions, it can effectively improve the ionic conductivity of the positive electrode active material on the one hand, and prevent direct contact with the electrolyte on the other hand to avoid the occurrence of side reactions. Vanadium and oxygen elements are evenly dispersed in the outer layer of the body, effectively improving the conductivity, structural stability, and thermal stability of the material, thereby significantly improving the cycle performance and rate performance of the material.

[0063] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned positive electrode active material. According to an embodiment of the present invention, the method comprises:

[0064] S100: mixing a hydroxide precursor with a lithium source, and sintering for the first time to obtain a body, wherein the hydroxide precursor includes Ni element, Co element, Mn element and optionally M element.

[0065] According to an embodiment of the present invention, the hydroxide precursor is prepared by the following method:

[0066] Nickel, cobalt, manganese and optionally a mixed salt of M are dissolved in water, and the pH value is adjusted to alkaline to obtain a precipitate, which is a hydroxide precursor.

[0067] Specifically, nickel, cobalt, manganese and optionally M mixed salt are taken in a stoichiometric ratio, and ammonia water is pumped into a synthesis kettle at the same time, sodium hydroxide or sodium carbonate solution is added to adjust the pH to 11-13, and a coprecipitation method is adopted while controlling factors such as temperature, stirring speed, solid-liquid ratio, and feeding speed. After overflowing from the synthesis kettle, the mixture is stirred, aged, centrifuged, washed, and dried to obtain a nickel-cobalt-manganese hydroxide precursor.

[0068] According to an embodiment of the present invention, the total molar concentration of the nickel ions, cobalt ions, manganese ions and optionally M ions is 0.3 mol / L-4.0 mol / L, for example, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, etc., and the soluble nickel, cobalt and manganese salts are sulfates. The concentration of the ammonia solution in the reactor is 0.5-3 g / L, for example, 0.5 g / L, 1 g / L, 2 g / L, 3 g / L, etc.;

[0069] The coprecipitation reaction temperature is 55-65°C, for example, 55°C, 60°C, 65°C, etc.;

[0070] The stirring speed is 120-300 r / min, for example, 120 r / min, 200 r / min, 250 r / min, 300 r / min, etc., and the time is 8-24 h, for example, 8 h, 10 h, 20 h, 24 h, etc.;

[0071] The feeding speed of the mixed solution is 80-120 mL / h, for example, it can be 80 mL / h, 90 mL / h, 100 mL / h, 120 mL / h, etc.

[0072] The solid-to-liquid ratio of the ammonia solution and the carbonate precipitant in the reactor is 80-130 g / L, for example, 80 g / L, 90 g / L, 100 g / L, 130 g / L, etc.

[0073] The stirring aging temperature is 30-70°C, for example, it can be 30°C, 50°C, 70°C, etc.; the time is 8-24h, for example, it can be 8h, 10h, 20h, 24h, etc.; the washing is alternating washing with deionized water and ethanol for more than 3 times, the drying temperature is 80-130°C, 80°C, 100°C, 130°C, etc., for example, the time can be 12-24h, for example, it can be 12h, 15h, 20h, 24h, etc.

[0074] S200: mixing a hydroxide precursor with a lithium source, and sintering for the first time to obtain a body, wherein the hydroxide precursor includes Ni element, Co element, Mn element and optionally M element.

[0075] According to an embodiment of the present invention, the lithium source includes one of lithium carbonate and lithium hydroxide; the molar ratio of the nickel cobalt manganese hydroxide precursor to Li in the lithium source is 1:1.01-1.05, for example, 1:1.01, 1:1.03, 1:1.05, etc.

[0076] According to an embodiment of the present invention, the temperature of the first sintering is 700°C-900°C, for example, it can be 700°C, 800°C, 900°C, etc. Controlling the temperature of the first sintering within the above range is beneficial to obtaining a body with a smooth surface of primary particles, improving the stability of the positive electrode active material, and further improving its cycle performance.

[0077] S300: mixing the main body with the material containing the coating layer and water, heating and stirring until the water is evaporated, and sintering for the second time to obtain a positive electrode active material.

[0078] By mixing the main body with the material containing the coating layer and water, a uniform coating layer can be formed on the surface of the main body, and the thickness of the first coating layer and the second coating layer can be easily controlled, so that the coating layer can prevent the body particles from peeling off, reduce the contact area between the main body and the electrolyte, and inhibit side reactions without affecting the transmission of lithium ions, thereby improving the stability of the positive electrode active material and thus improving the cycle performance of the battery containing it.

[0079] According to an embodiment of the present invention, the ratio of the mass of the body, the mass of the material containing the coating layer and the volume of the water is 1g: (0.01-0.12) g: 100 mL, for example, it can be 1g: 0.01g: 100 mL, 1g: 0.05g: 100 mL, 1g: 0.07g: 100 mL, 1g: 0.1g: 100 mL, 1g: 0.12g: 100 mL, etc. By controlling the ratio of the three within the above range, the thickness of the first coating layer and the second coating layer can be within the required range, so that the surface concavity of the positive electrode active material is moderate, and the cycle performance of the battery containing it can be improved. According to other embodiments of the present invention, the ratio of the mass of the body, the mass of the material containing the coating layer and the volume of the water is 1g: (0.03-0.10) g: 100 mL.

[0080] According to an embodiment of the present invention, the first sintering and the second sintering use purified compressed air as the reaction atmosphere, and the oxygen concentration of the compressed air is about 19.5-21.5%.

[0081] According to an embodiment of the present invention, the temperature of the second sintering is 200°C-600°C, for example, it can be 200°C, 300°C, 400°C, 500°C, 600°C, etc. By controlling the temperature of the second sintering within the above range, the thickness of the first coating layer and the second coating layer can be controlled within the required range, thereby improving the capacity and stability of the positive electrode active material, thereby improving the cycle performance of the battery containing it. According to other embodiments of the present invention, the temperature of the second sintering is 300°C-500°C.

[0082] According to an embodiment of the present invention, the time of the second sintering is 2h-10h, for example, it can be 2h, 5h, 8h, 10h, etc. By controlling the time of the second sintering within the above range, the thickness of the first coating layer and the second coating layer can be further controlled within the desired range, thereby reducing the probability of the substance in the coating layer entering the interior of the ternary material, thereby increasing the capacity and stability of the positive electrode active material, and thereby improving the cycle performance of the battery containing it.

[0083] According to an embodiment of the present invention, the coating-containing material includes polyvanadate. Since the polyvanadate has a clear structure and nanoscale size, the structure and charge can be regulated by reaction conditions. After a second calcination, the thickness of the first coating layer and the second coating layer can be controlled, thereby realizing the formation of composite materials of different particle sizes. The ternary material coated with lithium vanadium oxide is obtained by the above method. The polyvanadate has a better coating effect after in-situ pyrolysis. Vanadium and oxygen elements are evenly dispersed in the outer layer of the ternary material, which effectively improves the conductivity, structural stability, and thermal stability of the material, thereby significantly improving the cycle performance and rate performance of the material.

[0084] According to an embodiment of the present invention, the polyvanadate comprises Na6V 10 O 28 12H2O, K6V 10 O 28 At least one of 9H2O and NH4VO3. The polyvanadate is used to pyrolyze the polyvanadate uniformly dispersed on the surface of the body through the dispersion medium water to form a ternary material coated with lithium vanadium oxide, which further improves the conductivity, structural stability and thermal stability of the material, thereby significantly improving the cycle performance and rate performance of the material.

[0085] According to an embodiment of the present invention, the heating temperature is 100°C-200°C. For example, it can be 100°C, 130°C, 150°C, 170°C, 200°C, etc. By controlling the heating temperature within the above range, the evaporation rate of water can be effectively controlled, and a uniform coating layer with appropriate thickness is prepared on the surface of the body, thereby improving the capacity and stability of the positive electrode active material, thereby improving the capacity and cycle performance of the battery containing it.

[0086] According to an embodiment of the present invention, the stirring speed is 60r / min-600r / min, for example, it can be 60r / min, 100r / min, 300r / min, 500r / min, 600r / min, etc. By controlling the stirring speed within the above range, the evaporation rate of water can be effectively controlled, and a uniform coating layer with appropriate thickness can be prepared on the surface of the body, thereby improving the capacity and stability of the positive electrode active material, thereby improving the capacity and cycle performance of the battery containing it.

[0087] In summary, the positive electrode active material obtained by the above method can control the thickness of the first coating layer and the second coating layer on the surface of the main body of the positive electrode active material, as well as the roughness of the surface of the positive electrode active material, so that the coating layer can prevent the main body particles from peeling off and reduce the contact area between the main body and the electrolyte without affecting the transmission of lithium ions, thereby improving the stability of the positive electrode active material, and then improving the capacity and cycle performance of the battery containing it.

[0088] The method for preparing the positive electrode active material provided by the invention has fewer process flows and better coating effect.

[0089] In a third aspect of the present invention, the present invention provides a positive electrode sheet. According to an embodiment of the present invention, the positive electrode sheet comprises the positive electrode active material described in the first aspect of the present invention, or the positive electrode active material prepared by the method described in the second aspect.

[0090] According to an embodiment of the present invention, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, the positive electrode active material layer includes the above-mentioned positive electrode active material, wherein the positive electrode collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode collector can be aluminum foil.

[0091] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.

[0092] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0093] According to some embodiments of the present invention, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0094] It should be noted that the features and advantages described above for the positive electrode active material and the preparation method thereof are also applicable to the positive electrode plate and will not be described in detail here.

[0095] In a fourth aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery comprises at least one of the positive electrode sheets described in the third aspect.

[0096] As an example, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is located between the positive electrode sheet and the negative electrode sheet. During the charge and discharge process of the battery, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0097] According to an embodiment of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, wherein the negative electrode current collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode current collector can be a copper foil.

[0098] According to some embodiments of the present invention, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, and the like.

[0099] According to some embodiments of the present invention, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0100] According to some embodiments of the present invention, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0101] According to some embodiments of the present invention, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0102] According to some other embodiments of the present invention, there is no particular restriction on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. As an example, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film without particular restriction. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different without particular restriction.

[0103] According to some other embodiments of the present invention, the type of electrolyte is not specifically limited and can be selected according to needs. For example, the electrolyte can be in a gel state or a fully solid state. According to some specific embodiments of the present invention, the electrolyte is an electrolyte solution, and the electrolyte solution includes a lithium salt and a solvent.

[0104] According to some specific embodiments of the present invention, the lithium salt may include at least one of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium trifluoromethylsulfonate or lithium bis(trifluoromethylsulfonyl)imide.

[0105] According to some specific embodiments of the present invention, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone or diethyl sulfone.

[0106] In some embodiments of the present application, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0107] In a fifth aspect of the present invention, the present invention provides an electric device. According to an embodiment of the present invention, the electric device includes the above-mentioned battery. According to an embodiment of the present invention, the electric device may include but is not limited to a mobile phone, a laptop computer, an electric vehicle, etc.

[0108] It should be noted that the features and advantages described above for the battery are also applicable to the electrical device and will not be repeated here.

[0109] Below, the embodiment of the present invention is described. The embodiment described below is exemplary, is only used to explain the present invention, and cannot be interpreted as limiting the present invention. If no specific technology or conditions are indicated in the embodiment, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.

[0110] Example 1

[0111] (1) 2L of 2mol / L (total molar concentration of nickel, cobalt and manganese) mixed sulfate of nickel, cobalt and manganese, 2mol / L ammonia water and 4mol / L sodium carbonate, and 100mL of 0.85% aluminum oxide sol are simultaneously pumped into a synthesis reactor, wherein the molar ratio of nickel, cobalt and manganese is 50%:20%:30%, and a coprecipitation method is adopted at a temperature of 60°C; the stirring speed is 120r / min, and after overflowing from the synthesis reactor, the feeding speed is 110mL / h, and the aging temperature is stirred at 70°C for 20h, and the mixture is washed alternately with deionized water and ethanol for 4 times, and dried at 80°C for 12h to obtain a nickel-cobalt-manganese hydroxide precursor;

[0112] (2) 1 g of the obtained nickel-cobalt-manganese hydroxide precursor was mixed with 0.46 g of lithium hydroxide monohydrate, ground, calcined for the first time at 900° C., crushed, and cooled to obtain a nickel-cobalt-manganese oxide lithium material (body).

[0113] (3) 1.0 g of the obtained lithium nickel cobalt manganese oxide material and 0.05 g of Na6V 10 O 28 12H2O was added to 100 mL of water, stirred at 200 r / min, evaporated to dryness at 160°C, sintered for a second time at 450°C for 8 h, cooled to room temperature, and sieved to remove iron to obtain a vanadium lithium oxide-coated nickel cobalt manganese oxide material.

[0114] Example 2

[0115] The steps are basically the same as those in Example 1, except that in step (2), 0.41 g of lithium carbonate is mixed with 1.0 g of nickel cobalt manganese hydroxide precursor and ground, calcined at 900° C. for the first time, crushed, and cooled to obtain a nickel cobalt manganese oxide lithium material. In step (3), 1 g of nickel cobalt manganese oxide lithium material and 0.05 g of K6V 10 O 28 9H2O was added into 100mL of water to finally obtain lithium nickel cobalt manganese oxide material coated with lithium vanadium oxide.

[0116] Example 3

[0117] The steps are basically the same as those in Example 2, except that 1.0 g of lithium nickel cobalt manganese oxide material and 0.1 g of K6V 10 O 28 9H2O was added into 100mL of water to finally obtain lithium nickel cobalt manganese oxide material coated with lithium vanadium oxide.

[0118] Example 4

[0119] The steps are basically the same as those in Example 2, except that 1.0 g of lithium nickel cobalt manganese oxide material and 0.075 g of K6V 10 O 28 9H2O was added into 100mL of water to finally obtain lithium nickel cobalt manganese oxide material coated with lithium vanadium oxide.

[0120] Example 5

[0121] The steps are basically the same as those in Example 2, except that 1.0 g of lithium nickel cobalt manganese oxide material and 0.120 g of K6V 10 O 28 12H2O was added into 100mL of water to finally obtain lithium nickel cobalt manganese oxide material coated with lithium vanadium oxide.

[0122] Example 6

[0123] The steps are basically the same as those in Example 2, except that 1.0 g of lithium nickel cobalt manganese oxide material and 0.025 g of K6V 10 O 28 12H2O was added into 100mL of water to finally obtain lithium nickel cobalt manganese oxide material coated with lithium vanadium oxide.

[0124] Example 7

[0125] The steps are basically the same as those in Example 4, except that the temperature of the second sintering in step (3) is 200° C., and finally a nickel cobalt manganese oxide material coated with lithium vanadium oxide is obtained.

[0126] Example 8

[0127] The steps are basically the same as those in Example 4, except that the temperature of the second sintering in step (3) is 600° C., and finally a nickel cobalt manganese oxide material coated with lithium vanadium oxide is obtained.

[0128] Example 9

[0129] The steps are basically the same as those in Example 4, except that in step (3), 1.0 g of lithium nickel cobalt manganese oxide material and 0.075 g of NH4VO3 are added to 100 mL of water to finally obtain lithium nickel cobalt manganese oxide coated with lithium vanadium oxide.

[0130] Comparative Example 1

[0131] The steps are basically the same as those in Example 2, except that step (3) is deleted.

[0132] Comparative Example 2

[0133] The steps are basically the same as those in Example 2, except that 1.0 g of lithium nickel cobalt manganese oxide material and 0.0075 g of K6V 10 O 28 12H2O was added into 100mL of water to finally obtain lithium nickel cobalt manganese oxide material coated with lithium vanadium oxide.

[0134] Comparative Example 3

[0135] The steps are basically the same as those in Example 2, except that 1.0 g of lithium nickel cobalt manganese oxide material and 0.15 g of K6V 10 O 28 12H2O was added into 100mL of water to finally obtain lithium nickel cobalt manganese oxide material coated with lithium vanadium oxide.

[0136] The parameters for preparing the positive electrode active materials in the above examples and comparative examples are specifically shown in Table 1.

[0137] Table 1

[0138]

[0139]

[0140] After measurement, the chemical formula of the main body of the positive electrode active material of each embodiment and comparative example is shown in Table 2:

[0141] Table 2

[0142] Chemical formula of the substance Example 1 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Example 2 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Example 3 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Example 4 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Example 5 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Example 6 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Example 7 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Example 8 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Example 9 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Comparative Example 1 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Comparative Example 2 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]> Comparative Example 3 <![CDATA[LiNi 0.5 What 0.2 Mn 0.3 Al 0.001 O2]]>

[0143] The performance parameters of the positive electrode active materials prepared in the above examples and comparative examples are shown in Table 3:

[0144] Table 3

[0145]

[0146]

[0147] The average thickness difference = the average thickness of the second coating layer - the average thickness of the first coating layer.

[0148] (1) Scanning electron microscopy was performed on the positive electrode active material prepared in Example 1 to obtain Figure 1 ,Depend on Figure 1 It can be seen that the first surface of the primary particles and the gaps (second surface) between adjacent primary particles have a coating layer.

[0149] (2) Weigh the above-mentioned positive electrode active material, conductive carbon black, and binder PVDF in a ratio of 90:5:5, pour the above-mentioned substances into a dry agate mortar, and grind until there is no obvious stratification. The stirred slurry is evenly coated on the surface of the aluminum foil strip, dried, compacted, weighed, and vacuum-baked at 65°C for 15 hours. The positive electrode sheet, electrolyte (lithium salt is lithium hexafluorophosphate) and diaphragm, lithium sheet, gasket, shrapnel, and negative electrode shell are pressed and sealed to form a button battery.

[0150] ICP was used to test the vanadium content in the positive electrode material, and a button battery was made. At 25°C, the battery was charged at a constant current of 0.1C to the upper limit of the charge and discharge cut-off voltage, and then charged at a constant voltage to a current less than or equal to 0.05 mA, then left for 2 minutes, and then discharged at a constant current of 0.1C to the lower limit of the charge and discharge cut-off voltage. The discharge capacity at this time is the initial gram capacity of the button battery. At 25°C, the lithium ion button batteries assembled from the above Examples 1-9 and Comparative Examples 1-3 were tested at 25°C and 3.3-4.3V for the 0.1C / 0.1C first charge and discharge efficiency and the capacity retention rate after 200 cycles of 0.1C / 0.1C, and the values ​​are shown in Table 4.

[0151] Figure 2 This is a voltage curve diagram of the second cycle of the battery obtained in Example 2 of the present application under 0.1C charge and discharge conditions. It can be seen that the battery in Example 2 of the present application has a higher discharge specific capacity under 0.1C charging conditions.

[0152] Figure 3 This is a graph of the discharge specific capacity of the battery in Example 4 of the present application at different rates and cycle numbers. It can be seen that the battery containing the positive electrode active material of the present application has excellent specific capacity and rate performance.

[0153] Figure 4 It is a cycle performance diagram of Example 4 of the present application and Comparative Example 1. It can be seen that the cycle performance of the battery obtained by the positive electrode active material of Example 4 of the present application is significantly better than that of Comparative Example 1.

[0154] Table 4

[0155]

[0156] It can be seen from Table 4 that the lithium-ion battery prepared using the positive electrode active material prepared in the embodiment of the present invention has a high discharge specific capacity and capacity retention rate.

[0157] From Table 1 to Table 4, compared with Example 4, the coating material K6V in Example 5 10 O 28 As the amount of 9H2O added increases, the gaps between the primary particles are filled with too much of the second coating layer, which reduces the specific surface area BET2 of the positive electrode active material and reduces the concavity and convexity of the positive electrode active material, affecting the lithium ion transmission, resulting in a decrease in the specific capacity and cycle capacity retention rate of the battery. Similarly, the coating material K6V in Example 6 10 O 28 ·The amount of 9H2O added is reduced, the gaps between the primary particles are filled with too little second coating layer, the average thickness of the coating layer is also thinned, BET2 is too large, the convexity is large, and due to the thinning of the coating layer, the peeling of the main particles and the isolation of the electrolyte are weakened, so that the specific capacity and capacity retention rate of the battery are reduced; the temperature of the second sintering in step (3) of Example 7 is reduced, so that the first coating layer and the second coating layer are unevenly distributed, BET2 is large, the convexity is large, and the lithium ion transmission is affected, so that the specific capacity and capacity retention rate of the battery are reduced; the temperature of the second sintering in step (3) of Example 8 is increased, The elements in the material containing the coating layer penetrate and dope into the main body, so that some micropores on the surface of the main particles are completely covered by the coating layer. At the same time, the primary particles on the surface of the secondary particles will expand after being doped with the coating elements, and the gap between the primary particles will become smaller, which makes the BET2 smaller after coating and the convexity too small, so that the specific capacity and capacity retention rate of the battery are reduced; the material NH4VO3 containing the coating layer in Example 9 has poor solubility, resulting in uneven distribution of the coating layer, excessive BET2 after coating, and excessive convexity, resulting in incomplete discharge of the battery, so that the initial discharge capacity of the battery is low, and the battery cycle discharge retention rate is lower than that of Example 4.

[0158] From Tables 1 to 4, compared with Example 4, the body in Comparative Example 1 does not contain a coating layer, the particles of the body are prone to cracks and damage, and are prone to side reactions with the electrolyte, and the capacity and cycle performance of the battery containing it are poor; the coating material K6V in Comparative Example 2 10 O 28 · The amount of 9H2O added is too little, the gaps between the primary particles are filled with too little second coating layer, BET2 is too large, and the concave-convexity is too large, resulting in poor specific capacity and capacity retention rate of the battery; in comparative example 3, the coating material K6V 10 O 28 Too much 9H2O is added, the coating layer on the surface of the main particles is too thick, the distribution uniformity becomes poor, the BET2 is too large, the concave-convexity is too large, and the coating layer is too thick, which affects the lithium ion transmission, and also makes the battery specific capacity and cycle performance poor.

[0159] In summary, it can be seen from the above results that the lithium-ion battery prepared using the core-shell structure positive electrode active material prepared in the embodiment of the present invention has a high discharge specific capacity and capacity retention rate.

[0160] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0161] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material includes a body and a coating layer formed on at least part of the surface of the body, the body is a secondary particle formed by agglomeration of primary particles, the coating layer includes a first coating layer and a second coating layer, the first coating layer is formed on at least part of the first surface of the primary particle, and the second coating layer is formed on the second surface of the primary particle; The average thickness of the first coating layer is 0.5nm-10nm, the average thickness of the second coating layer is 3nm-20nm, and the average thickness of the second coating layer is greater than the average thickness of the first coating layer.

2. The positive electrode active material according to claim 1, characterized in that The average thickness of the first coating layer is 2nm-5nm; Optionally, the average thickness of the second coating layer is 5nm-12nm; Optionally, the difference between the average thickness of the second coating layer and the average thickness of the first coating layer is 2.0 nm-15.0 nm, preferably 3 nm-7 nm; Optionally, the coating layer has an average thickness of 1 nm to 20 nm, preferably 2 nm to 6 nm.

3. The positive electrode active material according to claim 1 or 2, characterized in that: The concavity and convexity of the positive electrode active material R=(BET2-BET1) / BET1, wherein BET2 is the specific surface area of ​​the positive electrode active material measured by the N2 adsorption method, BET1=6 / (ρ×Dv50), ρ is the tap density of the positive electrode active material, and Dv50 is the median particle size of the particle size volume distribution of the positive electrode active material; The concavity and convexity R=0.1-2.0, preferably 0.3-0.

8.

4. The positive electrode active material according to claim 3, characterized in that BET2=0.3m 2 / g-0.9m 2 / g, preferably 0.4m 2 / g-0.5m 2 / g; Optionally, BET1 = 0.23 m 2 / g-0.4m 2 / g; Optionally, ρ = 1.5 g / cm 3 -2.9g / cm 3 ; Optionally, Dv50=3 μm-18 μm.

5. The positive electrode active material according to claim 1 or 2, characterized in that: The body includes Li 1+ a Ni x Co y Mn z M w O2, wherein M includes at least one of V, Ti, W, Mg, Y, Zr, and Al, -0.1≤a≤0.2, 0.5≤x<1.0, 0<y≤0.2, 0<z≤0.3, 0≤w≤0.015; Optionally, the coating layer comprises lithium vanadium oxide.

6. A method for preparing the positive electrode active material according to any one of claims 1 to 5, characterized in that: include: Mixing a hydroxide precursor with a lithium source and sintering for the first time to obtain a body, wherein the hydroxide precursor includes Ni element, Co element, Mn element and optionally M element; The main body is mixed with the material containing the coating layer and water, heated and stirred until the water is evaporated, and sintered for the second time to obtain the positive electrode active material.

7. The method according to claim 6, characterized in that The ratio of the mass of the body, the mass of the material containing the coating layer and the volume of the water is 1 g: (0.01-0.12) g: 100 mL, preferably 1 g: (0.03-0.10) g: 100 mL; Optionally, the temperature of the second sintering is 200°C-600°C, preferably 300°C-500°C.

8. The method according to claim 6 or 7, characterized in that: The coating-containing material includes polyvanadate; Optionally, the polyvanadate comprises Na6V 10 O 28 12H2O, K6V 10 O 28 At least one of 9H2O and NH4VO3.

9. The method according to claim 6 or 7, characterized in that: The temperature of the first sintering is 700°C-900°C; Optionally, the heating temperature is 100°C-200°C; Optionally, the stirring speed is 60r / min-600r / min; Optionally, the second sintering time is 2h-10h.

10. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 5.

11. A battery, characterized in that: Including the positive electrode sheet as described in claim 10.

12. An electrical equipment, characterized in that: Comprising the battery of claim 11.